Time course of neuroinflammation after human stroke - a pilot study using co-registered PET and MRI - D'Anna, Lucio; Searle, Graham; Harvey, Kirsten; Matthews, Paul M.; Veltkamp, Roland (BMC neurology, 2023)
Background: Microglial activation contributes to both inflammatory damage and repair in experimental ischemic stroke. However, because of the logistical challenges, there have been few clinical imaging studies directly describing inflammatory activation and its resolution after stroke. The purpose of our pilot study was to describe the spatio-temporal profile of brain inflammation after stroke using 18kD translocator protein (TSPO) positron emission tomography (PET) with magnetic resonance (MR) co-registration in the subacute and chronic stage after stroke. Methods: Three patients underwent magnetic resonance imaging (MRI) and PET scans with TSPO ligand [11C]PBR28 15 ± 3 and 90 ± 7 days after an ischaemic stroke. Regions of interest (ROI) were defined on MRI images and applied to the dynamic PET data to derive regional time-activity curves. Regional uptake was quantified as standardised uptake values (SUV) over 60 to 90 min post-injection. ROI analysis was applied to identify binding in the infarct, and in frontal, temporal, parietal, and occipital lobes and cerebellum excluding the infarcted area. Results: The mean age of participants was 56 ± 20.4 years and mean infarct volume was 17.9 ± 18.1 ml. [11C]PBR28 showed increased tracer signal in the infarcted area compared to non-infarcted areas of the brain in the subacute phase of stroke (Patient 1 SUV 1.81; Patient 2 SUV 1.15; Patient 3 SUV 1.64). [11C]PBR28 uptake returned to the level of non-infarcted areas at 90 days Patient 1 SUV 0.99; Patient 3 SUV 0.80). No additional upregulation was detected elsewhere at either time point. Conclusions: The neuroinflammatory reaction after ischaemic stroke is limited in time and circumscribed in space suggesting that post-ischaemic inflammation is tightly controlled but regulatory mechanisms.